2014
DOI: 10.1021/jm401731q
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Trifluoromethyl(pyrimidin-2-yl)azetidine-2-carboxamides as Potent, Orally Bioavailable TGR5 (GPBAR1) Agonists: Structure–Activity Relationships, Lead Optimization, and Chronic In Vivo Efficacy

Abstract: Activation of the G-protein coupled receptor (GPCR) Takeda G-protein receptor 5 (TGR5), also known as G-protein bile acid receptor 1 (GPBAR1), has been shown to play a key role in pathways associated with diabetes, metabolic syndrome, and autoimmune disease. Nipecotamide 5 was identified as an attractive starting point after a high-throughput screen (HTS) for receptor agonists. A comprehensive hit-to-lead effort culminated in the discovery of 45h as a potent, selective, and bioavailable TGR5 agonist to test in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…Therefore, TGR5 activation provides a promising strategy for treatment of type 2 diabetes mellitus and associated metabolic disorders 10 11 12 . Thus TGR5 has drawn considerable attention from both academia and industry 13 14 15 16 17 18 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, TGR5 activation provides a promising strategy for treatment of type 2 diabetes mellitus and associated metabolic disorders 10 11 12 . Thus TGR5 has drawn considerable attention from both academia and industry 13 14 15 16 17 18 .…”
mentioning
confidence: 99%
“…1 ) causes smooth-muscle relaxation, prevents bile secretion, and greatly increases gallbladder volume 14 19 20 . Several absorbed TGR5 agonists have been shown to change heart rate and blood pressure in dogs 15 21 22 . Therefore, it was suggested that localized activation of TGR5 within the intestinal tract while avoiding systemic exposure (i. e. intestinally-targeted) could be a promising anti-diabetes mellitus strategy with minimal side effects 23 24 .…”
mentioning
confidence: 99%
“…Therefore, the no-observed, adverse-effect level of RDX8940 in the 7-day dose-range-finding study was determined to be 300 mg·kg −1 ·day −1 , which produced no significant effects on organ weights or histological findings. Pathologies of known TGR5 agonists (19, 28, 29), seen in preclinical animal studies, including cardiac, hepatic, and pancreatic toxicities, were not observed.…”
Section: Resultsmentioning
confidence: 94%
“…TGR5 agonists may have therapeutically beneficial effects in patients with NAFLD/NASH via stimulation of GLP-1 and GLP-2 production (31, 35). However, clinical development of TGR5 agonists for the treatment of metabolic diseases has been hindered by side effects associated with systemic TGR5 agonism, including inhibition of gallbladder emptying (5, 22), which can lead to gallstone formation, and changes in heart rate and blood pressure (28, 29). Therapeutically targeting intestinal TGR5 with molecules that are not systemically absorbed could potentially avoid these unwanted side effects by preventing activation of TGR5 receptors expressed in tissues elsewhere in the body, such as the gallbladder.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence: effect of ASO in DIO mice [179] TGR5 receptor: its activation leads to secretion of GLP-1 and other related incretins in gut enteroendocrine cells and to a decrease in LPS Th1 cytokines like TNF-α and IL-12 in monocytes/macrophages and dendritic cells. Evidence: low MW compounds activity in ob/ob mice (target: Type 2 diabetes) [180] Agonists to hNMU receptors. Evidence: KO mouse.…”
Section: Targetmentioning
confidence: 99%